THE INFLUENCE OF COMMUNICATION, MOTIVATION, AND THE ENVIRONMENT PHYSICAL WORK ON EMPLOYEES' WORK SPIRIT SECRETARIAT OF THE DIRECTORATE GENERAL OF HOUSING MINISTRY OF PUPR - Tehninabenua, Tracy; Farida, Ida (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study was to examine the effect and nature of the relationship between work enthusiasm and three influences, namely communication, motivation and physical work environment on work enthusiasm. This research was conducted at the Secretariat of The Directorate General of Housing, Ministry Of PUPR. The research method used in this research is descriptive research and causal research. The sample in this study found 54 employees using non-probability sampling technique. Where the data comes from primary data collected through a questionnaire with a Likert scale. And the data analysis method in this study is multiple linear regression. The results showed that Communication, Motivation and Physical Work Environment had a positive effect on Work Enthusiasm.